Live nondirected uterus donors: Psychological characteristics and motivation for donation. Issue 5 (13th February 2018) - Warren, A. M.; Testa, G.; Anthony, T.; McKenna, G. J.; Klintmalm, G. B.; Wallis, K.; Koon, E. C.; Gunby, R. T.; Johannesson, L.
Abstract : Emerging research suggests that uterus transplantation is a viable option for women without a uterus who want to become pregnant and carry a child to term. Currently, no knowledge exists regarding nondirected uterus donors. This study (NCT 02656550) explored the baseline psychological characteristics of nondirected uterus donors at a single study site. Of the 62 potential donors who underwent initial screening, 6 nondirected donors were chosen and participated in uterus donation. Participants received a comprehensive evaluation, which included clinical history and psychological assessments. The mean age of the donors was 42 years; most (83%) were white/not Hispanic, and all had a college degree. Current depression was reported by 2 participants, past depression was reported in 2 participants, and past anxiety was reported in 3 participants. Based on several different psychological measures, donors had a higher general well‐being than the normative sample, and none of the participants' scores indicated psychological distress. All 6 women indicated that giving another woman an opportunity to carry her own child was a motivation for pursuing uterus donation. Further research on potential psychological motives and gains for the donor as well as long‐term effects on donors is crucial for ethical practice. Abstract : This study describes the first cohort of nondirected living uterus donors, presenting donor participants with a higher health‐related quality of life than the general population at baseline, and with the greatest motivator for donation being a desire for another woman to carry her own child followed by a desire to contribute to science and to help others.